Liquid chromatography–mass spectrometry for C60 fullerene analysis: optimisation and comparison of three ionisation techniques - Li, Ling; Huhtala, Sami; Sillanpää, Markus; Sainio, Pirjo (Analytical and bioanalytical chemistry, 2012)
The increasing use and production of nanomaterials have led to growing concern over the release of new pollutants to the environment. Fullerenes have been a subject of intense research, both because of their unique chemistry and because of technological applications. The development of analytical methods to quantify the fullerenes in complex sample matrices is a crucial step in the study of their occurrence and exposure, and thus in risk assessment. This paper reports the development and optimisation of a method combining liquid chromatography with ion-trap mass spectrometry (LC–ITMS) for analysis of the fullerene C 60 . Under the optimised chromatogram conditions, a C 18 analytical column had good selectivity for fullerenes C 60 and C 70 , with retention times of 3.0 and 4.1 min, respectively. Mass spectrometric detection was tested and optimised using three common ionisation techniques—atmospheric-pressure chemical ionisation (APCI), atmospheric-pressure photoionisation (APPI), and electrospray ionisation (ESI). The molecular ion was most abundant for C 60 − ( m / z = 720) in APCI and APPI, whereas adduct ions were formed with the molecular ion in ESI. Finally, the performance of the three ionisation techniques examined was compared by use of five validation criteria. The instrument detection limit (8 ng mL −1 ), quantification limit (27 ng mL −1 ), detection sensitivity (90.2 ng mL −1 ), linear range (8–1,000 ng mL −1 ), and repeatability (15 %) of APPI make it the most promising ionisation technique for fullerene C 60 analysis.